"Chronic Disseminated Aspergillosis, " a Novel Fungal Immune Reconstitution Inflammatory Syndrome. (7th November 2020) - Pourbaix, Annabelle; Guery, Romain; Bruneau, Julie; Blanc, Estelle; Jouvion, Gregory; Weinandt, Marthe; Rouzaud, Claire; Lourenço, Jérémy; Boutboul, David; Mira, Jean-Paul; Rouquette, Alexandre; Molina, Thierry Jo; et al.
Abstract: We report a case of chronic hepatosplenic aspergillosis following immune reconstitution complicating colic aspergillosis in an AIDS patient with multicentric Castleman disease. Symptoms mimicked the clinical presentation of chronic disseminated candidiasis and responded to corticosteroid. This emerging entity enlarges the spectrum of fungal immune reconstitution inflammatory syndrome in the HIV setting.